2012
DOI: 10.1371/journal.pone.0041253
|View full text |Cite
|
Sign up to set email alerts
|

Two New Rapid SNP-Typing Methods for Classifying Mycobacterium tuberculosis Complex into the Main Phylogenetic Lineages

Abstract: There is increasing evidence that strain variation in Mycobacterium tuberculosis complex (MTBC) might influence the outcome of tuberculosis infection and disease. To assess genotype-phenotype associations, phylogenetically robust molecular markers and appropriate genotyping tools are required. Most current genotyping methods for MTBC are based on mobile or repetitive DNA elements. Because these elements are prone to convergent evolution, the corresponding genotyping techniques are subopt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
132
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(134 citation statements)
references
References 70 publications
2
132
0
Order By: Relevance
“…Although WGS is becoming cheaper, it is still too expensive to be used for routine genotyping of M. avium subspecies paratuberculosis isolates and requires robust data handling and analysis processes. Single nucleotide polymorphisms (SNPs) have been used successfully to type several genetically monomorphic pathogens, including M. tuberculosis (13), Mycobacterium bovis (14), Salmonella enteritica serovar Typhi (15), and Yersinia pestis (16). SNP assays have been used to discriminate between M. avium subspecies paratuberculosis strain types I, II, and III (17,18) and between strains derived from animal and human hosts (19).…”
mentioning
confidence: 99%
“…Although WGS is becoming cheaper, it is still too expensive to be used for routine genotyping of M. avium subspecies paratuberculosis isolates and requires robust data handling and analysis processes. Single nucleotide polymorphisms (SNPs) have been used successfully to type several genetically monomorphic pathogens, including M. tuberculosis (13), Mycobacterium bovis (14), Salmonella enteritica serovar Typhi (15), and Yersinia pestis (16). SNP assays have been used to discriminate between M. avium subspecies paratuberculosis strain types I, II, and III (17,18) and between strains derived from animal and human hosts (19).…”
mentioning
confidence: 99%
“…Since this typical spoligotype pattern has become a specific marker of the Beijing genotype, some PCR methods to detect this specific deletion, named region of difference 207 (RD207), have been developed (20)(21)(22). In addition to RD207, another deleted region named RD105 was also shown to be a good marker for discrimination of the Beijing genotype, although this deletion is common for all the east Asian lineages, including the non-Beijing strains (10,23); however, most of these published detection methods require expensive real-time PCR equipment and high-cost reagents (24). The conventional PCR assay targeting RD207 still seems to be at a disadvantage, since it relies on an unstable inser-tion sequence that is likely to be a target of homologous recombination.…”
mentioning
confidence: 99%
“…The conventional PCR assay targeting RD207 still seems to be at a disadvantage, since it relies on an unstable inser-tion sequence that is likely to be a target of homologous recombination. Instead of unstable repetitive structures, single nucleotide polymorphisms (SNPs) were recently considered to be a robust target for defining the accurate position of a strain on the phylogenetic tree, since horizontal gene transfer or gene recombination between different strains is rare in the M. tuberculosis complex (MTC) (12,24,25). Filliol et al (26) drew phylogenetic trees of the MTC using several typing methods and showed that the dendrogram drawn with SNPs most accurately reflected the true evolution of the MTC.…”
mentioning
confidence: 99%
“…Where there is a low IS6110 copy number, other typing methods must be employed to facilitate sufficient discrimination. Typing methods that rely on single nucleotide polymorphisms (SNPs) and polymorphic GC-rich repetitive sequences (PGRS) have proven to be effective [8][9][10].…”
Section: The Good…mentioning
confidence: 99%